An exploration of rural Chinese teachers' wellbeing: Insights from mixture modelling of latent profile analysis. Issue 1 (16th April 2022) - Cui, Bo; McCallum, Faye; White, Mathew A
The importance of teachers' wellbeing and the complexities of teaching are becoming more widely understood through the lens of positive psychology. For example, teachers' wellbeing and optimal functioning have an impact on their ability to teach effectively, teacher retention and their job satisfaction. However, there is a shortage of global research investigating teachers' wellbeing, especially in rural China. The current study contributes to this shortage through an appreciative inquiry to examine rural teachers' wellbeing in Jilin Province in rural China. Unlike earlier research, this study focused on the positive elements of rurality that strengthen teachers' wellbeing. A two-phase exploratory, sequential, mixed-methods design was adopted. This paper reports on quantitative findings of Stage 2 of the study, a latent profile analysis of 1, 198 participants' experiences of wellbeing. The results suggest there are five unique profiles that enable rural Chinese teachers' wellbeing: thriving, personally driven, surviving, career-driven and languishing. This study undertakes a novel approach of latent profile analysis of teachers' wellbeing in rural China. These findings have implications for policymakers, initial teacher education programs, and teacher wellbeing interventions.